First Isolation of Staphylococcus warneri from Cultured Rainbow Trout (Oncorhynchus mykiss) Broodstock in Turkey - Metin, S.; Kubilay, A.; Onuk, E. E.; Didinen, B. I.; Yildirim, P. (Eur Assoc Fish Pathologists, 2014)
In this study, Staphylococcus warneri was isolated for the first time in rainbow trout in Turkey. The outbreak occurred in broodstocks at a water temperature of 10 degrees C during February 2014. The outbreak was chronic, without mortalities. Infected trout typically exhibited emaciation, decreased mucus content, gray cloudy appearance on the flanks, blistering of the skin surface, erosive lesions on the base of the anal fins, discoloured liver, and petechial haemorrhage and lysis in muscle. Grampositive S. warneri was isolated from the anterior kidney, spleen, and liver of the diseased fish. S. warneri was identified based on morphological and biochemical features by using conventional methods and the API Staph system. The 16S rRNA gene sequence of strain STP02 (representative strain) was sequenced and showed high similarity (99.93%) with the type strain S. warneri ATCC 278361 (L37603) available in the GenBank debates.